2017
DOI: 10.1016/j.radcr.2017.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal esophageal hematoma precipitated by chronic idiopathic thrombocytopenic purpura

Abstract: Submucosal esophageal hematoma is an uncommon clinical entity. It can occur spontaneously or secondary to trauma, toxins, medical intervention, and in this case, coagulopathy. Management of SEH is supportive and aimed at its underlying cause. This article reports an 81-year-old male patient with chronic idiopathic thrombocytopenic purpura and hypertension that develops a submucosal esophageal hematoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Characteristic clinical manifestations of SH comprises dysphagia or odynophagia, acute chest pain, and hematemesis[ 3 ]. Typical cases of SH have been reported by several authors[ 1 , 2 , 4 ]. However, no cases of the SH extending from the hypopharynx to the lower esophagus caused by oral administration of hirudin and panax notoginseng powder have been reported, especially cases with atypical clinical manifestations.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Characteristic clinical manifestations of SH comprises dysphagia or odynophagia, acute chest pain, and hematemesis[ 3 ]. Typical cases of SH have been reported by several authors[ 1 , 2 , 4 ]. However, no cases of the SH extending from the hypopharynx to the lower esophagus caused by oral administration of hirudin and panax notoginseng powder have been reported, especially cases with atypical clinical manifestations.…”
Section: Introductionmentioning
confidence: 74%
“…Detailed and accurate acquisition of clinical data of patients, comprehensive physical examination combined with endoscopy, and CT are useful for accurate diagnosis. Risk factors for SH include female sex, hypertension, increased esophageal pressure, coagulopathy, and use of an anticoagulant[ 2 , 4 ]. It has been reported that elderly patients who are taking anticoagulant or antiplatelet medication are at higher risk for SH[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aetiology is either iatrogenic, following oesophageal instrumentation for endoscopy, nasogastric tube placement or endotracheal intubation; traumatic, due to foreign body or food bolus, forceful vomiting or dry retching; or spontaneous 2–5 . Anticoagulation, coagulopathy, female sex and advanced age are considered to be the main risk factors 6 …”
Section: Figurementioning
confidence: 99%
“…[2][3][4][5] Anticoagulation, coagulopathy, female sex and advanced age are considered to be the main risk factors. 6 Presentation of IOH can vary depending on the severity of bleeding, degree of oesophageal occlusion and underlying comorbidities. Triad of retrosternal chest pain, dysphagia and haematemesis can be present in up to 35% of patients, with 80% demonstrating two of the three signs.…”
mentioning
confidence: 99%